Points of view : (McGraw-Hill, 2004)
This comprehensive best-selling reader features contrasting viewpoints on current political debates and traditional topics of interest in contemporary American Government courses. By providing two opposing positions for each topic, Points of View challenges students to examine and appreciate differing perspectives